Bangabandhu and Bangladesh, Sharif uddin Ahmed (ed.), (Dhaka: The University Press Limited and North South University 2021), (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
Abstract not availableJournal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(1), 2023, pp. 147-152